About the Book «Higher Efficiency of Power-and-Heat Generation and Heat Supply Systems» - V. K. Balabanovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
The monograph contains generalized results of author’s investigations and practical work in respect of modernization of power-and-heat generation steam turbine plants with stage water heating.This book is intended for researchers, engineers and other technical personnel, lecturers, post graduates and students of heat power engineering specialities.